STATISTIKA NONPARAMETRIK: PENGGABUNGAN DIAGRAM POHON POLYA YANG BERHINGGA (NONPARAMETRIC STATISTICS: A MIXTURES OF FINITE POLYA TREES ) - , Asri Ode Samura ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis be explained an approach in nonparametric Bayesian, a mixture of Polya tree (MPT). MPT uses a partition of supports from a density of its original distribution. In general, the density keeps the original form of the distribution in every mixture of partition as well as adds a new parameter obtained from conditional probabilities. A model of Polya tree can be applied widely and also can be programmed easily by giving MCMC scheme to fit the original parametric model.